2017
DOI: 10.1108/ejtd-02-2017-0014
|View full text |Cite
|
Sign up to set email alerts
|

Adult learning theories: implications for online instruction

Abstract: Purpose This paper analyzes critically four selected learning theories and their role in online instruction for adults. Design/methodology/approach A literature review was conducted to analyze the theories. Findings The theory comparison revealed that no single theory encompasses the entirety of online instruction for adult learning; each theory explains some portion of adult online learning; theories are contextual; and components of all theories can be utilized to improve online learning. Research limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(85 citation statements)
references
References 46 publications
3
75
0
7
Order By: Relevance
“…E-learning approaches had not been adequately reported on the selected studies, therefore losing the opportunity for this approach to be trialled and evaluated, especially when they afford easy access (41) and are less expensive than face-to-face approaches (42). If the healthcare professionals gather interactive supervision, feedback and evaluation, they can achieve the same level of interpersonal skills development (43). Additionally, 'multi-professional' topics could be found in some of the studies, which has been seen as a positive approach (10), as they tended to be dominated by doctors and nurses' issues, which is in agreement with previous studies (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…E-learning approaches had not been adequately reported on the selected studies, therefore losing the opportunity for this approach to be trialled and evaluated, especially when they afford easy access (41) and are less expensive than face-to-face approaches (42). If the healthcare professionals gather interactive supervision, feedback and evaluation, they can achieve the same level of interpersonal skills development (43). Additionally, 'multi-professional' topics could be found in some of the studies, which has been seen as a positive approach (10), as they tended to be dominated by doctors and nurses' issues, which is in agreement with previous studies (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…Although the faculty members want honest feedback on their performance as teachers and evaluators, it is believed that this feedback has to be given anonymously for students to feel safe [ 22 ]. Some students indicated that it was difficult to disclose negative feedbacks in front of their faculty and prefer writing their comments in an anonymous survey.…”
Section: Discussionmentioning
confidence: 99%
“…Learner modeling leads to a personalized learning environment. Arghode et al (2017) explained that learners construct their own knowledge. Since adults bring their day today experiences and their needs to the instructional setting, a constructivist approach is more effective for the adult learning process.…”
Section: Learner Modeling/personalization Layermentioning
confidence: 99%
“…Since adults bring their day today experiences and their needs to the instructional setting, a constructivist approach is more effective for the adult learning process. The social constructivism theory emphasizes the effect of culture and context when constructing knowledge (Arghode et al, 2017).…”
Section: Learner Modeling/personalization Layermentioning
confidence: 99%